An overview of basic pathophysiological interactions between gut bacteria and their host - Simonson, Mathilde; Simonson, Thomas; Nobécourt, Estelle (Frontiers in Nutrition, 2025)
Sometimes referred to as a “forgotten organ,” the gut microbiome (GMB) of humans includes hundreds of commensal bacterial species, which carry several million genes and complement our physiology. Commensal bacteria break down indigestible dietary fiber and provide essential metabolites. These often have a dual action: as “stand-alone” chemicals (e.g., combustibles or emulsifiers) and as signaling molecules that influence host gene expression and physiology. A second function of gut bacteria is to help maintain the intestinal barrier, partly by conditioning the host immune system. Alteration and damage to the GMB have been linked to many pathologies. This review provides an introduction to the more basic mechanisms of GMB-host interaction. It focuses on (a) gut bacteria and their metabolites, and (b) the metabolites’ role in host gene regulation and homeostasis. To this end, recent articles were selected, along with some earlier ground-breaking articles. We consider microbiome composition and intestinal homeostasis, microbiome composition and dysbiosis, immune modulation, gut bacteria metabolite chemistry and host gene regulation.